P165 GUM/HIV trainees' experience and training needs in the management of patients disclosing sexual violence. (23rd May 2012) - Sacks, R; Coyne, K; Cybulska, B; Dhairyawan, R; Forster, G; Emerson, C; Mears, A; Mears, A; Shah, R; Spice, W
Abstract : Background: Patients attending GUM clinics may disclose sexual violence. Are GUM/HIV trainees equipped to manage these cases? Aim: To assess the experience and training needs of GUM/HIV trainees in managing patients disclosing sexual violence (SV patients). Method: An e-survey was open to GUM/HIV trainees for 12 weeks from February 2011. Data were analysed in Excel. Results: Of the 158 current GUM/HIV trainees, 44 (28%) completed surveys. All respondents managed SV patients and 59% managed ≥ 1 SV case/month. Of these, 98% had seen females, 66% males, 73% 16–17 years/olds, 34% 13–15 years/olds, 5% under-13s. All respondents routinely asking about SV saw ≥ 1 case/month vs 50% of those who rarely/never asked. Confidence increased with frequency of seeing patients: 96% (25/26) seeing ≥ 1 SV patient/month felt confident vs 67% (12/18) seeing <1/month. Confidence in managing female, male and under-18 SV patients was reported in 86%, 79% and 58% respectively. In the six units with a dedicated SV clinic two trainees had worked in one, overall, 92% would have liked to. Similarly, 14% had worked in a Sexual Assault Referral Centre, 81% would have liked to. Respondents had trained in safeguarding children, adult SV, chain of evidence, vulnerable adults and domestic violence in 92%, 82%, 76%, 64%, 32% respectively. Abstract P165 Table 1 details respondents' reported competencies and training availability in 2010 curriculum skills. Conclusions: Wide variation exists in reported SV experience, training received and training availability, in the 28% of trainees responding. Regular accessible training is needed in identifying and managing patients disclosing SV.